Modular order for the development of mechanical structures for electronic equipment practices. Sectional specification. Interface co-ordination dimensions for the 25 mm equipment practice. Detail specification. Dimensions for cabinets and racks Part 2-1, (15th April 1997) - British Standards Institution,
No abstract available